HUBUNGAN KESEPIAN DAN KECENDERUNGAN BERSELINGKUH PADA WANITA YANG MENJALANI HUBUNGAN PERNIKAHAN JARAK JAUH - Bramasto Bima Hendra; Ratriana Y. E. Kusumiati (Universitas Negeri Medan, 2020)
This study aims to examine the relationship of loneliness and the tendency to cheat on women who undergo long-distance marital relationships. The hypothesis of this study is that there is a positive relationship between loneliness and the tendency to have an affair in women undergoing long-distance marriages. Participants in this study amounted to 31 subjects obtained by accidental sampling technique, with the criteria of women undergoing long-distance marital relationships for at least two months. Data were collected on a lonely scale from Ucla Version 3 and the scale of cheating tendencies. Data analysis used Pearson correlation with the help of SPSS 23. The results showed a positive relationship between loneliness and the tendency to have an affair in women undergoing long-distance marriage (r = 0.501; p = 0.002).Keywords: Loneliness, Tendency To Cheat, Women Undergoing Long-Distance Marriage.